Chemoresistive xylene sensor based on hollow praseodymium oxide nanospheres - Zito, Cecilia A. [UNESP]; de Sá, Bruna S. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2024)
Praseodymium oxide has already been explored in several applications within materials science. Yet, its use as a chemoresistive gas sensor has rarely been reported. Herein, we present the aromatic hydrocarbon sensing performance of monoclinic Pr12O22 nanospheres produced via a microwave-assisted solvothermal approach with a subsequent calcination step. Sensing tests were performed at temperatures ranging from 200 to 500 °C and under different relative humidity conditions, from 0 % to 93 %. At 400 °C and dry conditions, the sensor exhibits a response of ca. 50 % towards 200 ppm m-xylene, which is much higher than those to benzene and toluene. The sensor also reveals excellent sensitivity for concentrations as low as 5 ppm of m-xylene, even at high relative humidity, while maintaining stability and repeatability over several days. Furthermore, the Pr12O22-based sensor presents an unusual p-type behavior attributed to the mixed valence states of the rare earth metal.
Keywords: Metal oxide; Pair distribution function; Pr6O11; Rare-earth; Volatile organic compounds